The Guarantee of Legal Certainty on The Issuance of A Building Use Land Rights Certificate (Case Study of The Decision of The State Administrative Court Number 30 / G / 2016 / PTUN. SMD) - Harum Bunga Salni (LEGAL BRIEF, 2022)
Article 19 Paragraph (1) of Law Number 5 of 1960 concerning Basic Regulations on Agrarian Principles instructs the government to carry out land registration activities throughout the territory of Indonesia in order to ensure legal certainty. The registration activity includes the provision of certificates of proof of rights that are valid as a strong evidence, which in this case is a certificate of land rights. However, in practice, the effectiveness of certificates in providing legal certainty and protection is still often questioned. In connection with this, there is a case raised by the author, namely a lawsuit by AM on the validity of the certificate of Hak Guna Bangunan on behalf of PT. KRA issued by the Balikpapan City Land Office. The problem in this research is how to guarantee legal certainty for the issuance of the certificate of Hak Guna Bangunan on behalf of PT. KRA? And how is the decision of the State Administrative Court Number 30/G/2016/PTUN.SMD in accordance with the provisions of the National Land Law? To answer these problems, a normative juridical research was conducted on the legal rules of land registration in Indonesia and the concepts of legal certainty. Data processing is carried out qualitatively and conclusions are drawn using a deductive mindset. The conclusion of the research is legal certainty over the issuance of a certificate of Hak Guna Bangunan on behalf of PT. KRA can be realized because of the efforts of legal discipline, both from PT. KRA as a legal entity and the Land Office as a representative of the government.